DIGITALIZATION OF TRADITIONAL PESANTREN: A LOW-COST EDTECH DEVELOPMENT STRATEGY TO ENHANCE SANTRI’S AUTONOMY AND DIGITAL SKILLS - Mufadhol Mufadhol; Mohammed Al-Harbi; Sultan Al-Qahtani (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Traditional pesantren remain one of the most influential and enduring educational institutions in Indonesia, yet many continue to operate with limited technological infrastructure. The rapid digital transformation in the national education system has intensified the need for pesantren to adopt low-cost, context-appropriate EdTech solutions to strengthen santri autonomy, digital literacy, and readiness for 21st-century learning demands. The research is grounded in the recognition that pesantren face structural barriers—including financial constraints, low teacher digital capacity, and limited access to digital devices—that hinder their participation in broader educational innovations. These gaps highlight the urgency of developing affordable, scalable, and culturally compatible digitalization strategies. The study aims to design and evaluate a low-cost EdTech development model tailored to pesantren environments, focusing on enhancing self-regulated learning, digital skills, and instructional efficiency. A mixed-methods approach is employed, combining needs assessment surveys, classroom observations, interviews with kyai and ustadz, and prototype testing of low-cost digital learning tools such as offline learning apps, modular LMS platforms, and open-source interactive media. The results indicate that low-cost EdTech integration significantly improves santri autonomy, with notable increases in self-directed learning scores and digital skill acquisition. Teachers report reduced workload and improved lesson organization, while santri demonstrate greater engagement through blended and peer-supported digital activities. Prototype testing shows that even minimal technological interventions—such as offline content repositories and basic digital task modules—yield substantial pedagogical benefits. The study concludes that digitalizing traditional pesantren does not require high-cost technological investments; rather, effective change emerges from strategic, culturally aligned, and scalable EdTech designs. Strengthening teacher training, developing open-source digital resources, and building sustainable school-level technology governance are essential for long-term implementation.